Lucy & Tom's Christmas - Hughes, Shirley (New York, N.Y., U.S.A. : Viking Kestrel, 1986)
Follows a young brother and sister as they wrap presents, hang paper chains, write letters to Santa, and wake up to many surprises on Christmas morning.
2.0
K-3
Keywords: Christmas -- Fiction; Family life -- Fiction; Christmas -- Fiction